IMMUNECARE: The Innovation of Basic Immunization Services with Android Application for Public Health Center in Palembang - Sari Wahyuni; Juwita Suryani; Elga Mardani (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
One of the main issues of the Ministry of Health of the Republic of Indonesia in 2019 is the scope of complete basic immunization. One of the problems in the implementation of basic immunization is rejection from the community due to a lack of communication and information from health workers or the media. Based on the results of a preliminary study at Alang-Alang Lebar Public Health Center and 23 Ilir Public Health Center Palembang in 2019, it was found that the utilization of the KIA book was low (81.8%), and there was a lack of mother’s knowledge of basic immunization (40.9%). Along with the development of the 4.0 industrial revolution that changes how humans work from manual to digitalization, an application can be used as a representation in public service. This study aimed to produce an android-based Immunecare application on basic immunization services. This study used a research and development model. The source of data for this study was obtained from mothers with children aged 0-11 months, midwives, material experts, and media experts. The results of the feasibility test for this application by a material expert was highly feasible (94%), media expert was feasible (73%), and field practitioners was feasible (72%). The results of the questionnaire on Immunecare application showed a very good category from mothers (73%) and showed a very good category from midwives (82%), and mothers with good knowledge (86.7%). This study concluded that the Immunecare application is feasible (79.6%) to be used on basic immunization services.